COMMUNICATIVE COMPETENCE IN PROFESSIONAL DENTIST ACTIVITIES - Манащук, Надежда; Черный, Наталия; Бойцанюк, Светлана (SWorldJournal, 2021)
The article describes the question of communicative competence as a component of the doctor’s professional activities. The practice of good communication skills in the medical profession is integral for the development of meaningful and trustworthy relati